A review of East Asian reports of aurorae and comets circa AD 775. Issue 6 (July 2015) - Chapman, J.; Neuhäuser, D.L.; Neuhäuser, R.; Csikszentmihalyi, M.
Abstract Given that a strong 14C variation in AD 775 has recently been suggested to be due to the largest solar flare ever recorded in history, it is relevant to investigate whether celestial events observed around that time may have been aurorae, possibly even very strong aurorae, or otherwise related to the 14C variation (e.g. a suggested comet impact with Earth's atmosphere). We critically review several celestial observations from AD 757 to the end of the 770s, most of which were previously considered to be true, and in some cases, strong aurorae; we discuss in detail the East Asian records and their wording. We conclude that probably none among the events after AD 770 was actually an aurora, including the event in AD 776 Jan, which was misdated for AD 774 or 775; the observed white qi phenomenon that happened above the moon in the south‐east was most probably a halo effect near the full Moon – too late in any case to be related to the 14C variation in AD 774/5. There is another report of a similar (or identical) white qi phenomenon above the moon, reported just before a comet observation and dated to AD 776 Jan; the reported comet observed by the Chinese was misdated to AD 776, but actually sighted in AD 767. Our critical review of East Asian reports of aurorae circa AD 775 shows some very likely true Chinese auroral displays observed and reported for AD 762; there were also several events prior to AD 771 that may have been aurorae but are questionable. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)